KENDALA GURU GEOGRAFI DALAM MEMANFAATKAN MEDIA PEMBELAJARAN DARING - Ita Fatimah; Khairani khairani (JURNAL BUANA, 2022)
This study aims to discusss the constraints and efforts of geography teachers in utilizing online learning media at 3 SMAN Bengkulu City. This study uses a qualitative method. Data collection techniques area interviews,observation, and documentation. The subjects of this study were 6 geogrphy teachers , 10 students, curriculum representatives and 3 guardiians. The result of the indicate that the obstacles for geography teachers in utilizing online learning media at SMAN 3 Bengkulu city. Are difficult material to coveny, interactions between educators and students do not run optimally, difficulties in correcting student assigments,limited uses of online learning media, difficulties in using learning media, online and inadequate internet signal and package. Efforts to overcome obstacles, namely the impostion of sanctions on students, teachers are allowed to correct to assignment with school computer and wifi and provide training to teachers in the use of online media.